2020
DOI: 10.1016/j.infpip.2020.100042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the FilmArray® multiplex PCR system and associated meningitis/encephalitis panel in the diagnostic service of a tertiary hospital

Abstract: Summary Rapid and accurate diagnosis of meningitis/encephalitis (M/E) is essential for successful patient outcomes. The FilmArray® meningitis/encephalitis Panel (MEP) is a multiplexed PCR test for simultaneous, rapid detection of pathogens directly from cerebrospinal fluid (CSF) samples. 94 prospectively collected CSF specimens from patients with clinical suspicion of infective M/E underwent testing for 14 pathogens simultaneously, including Escherichia coli , Haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
(23 reference statements)
1
13
1
Order By: Relevance
“…Macroscopic appearance of the CSF is reported. UHL laboratory protocols for CSF testing are similar to those reported previously in our study of the FilmArray ME panel [ 18 ]. Leucocytes and erythrocytes were quantified by manual microscopy using a KOVA Glasstic Slide counting chamber in which 1μl of CSF was assessed using manual light microscopy.…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…Macroscopic appearance of the CSF is reported. UHL laboratory protocols for CSF testing are similar to those reported previously in our study of the FilmArray ME panel [ 18 ]. Leucocytes and erythrocytes were quantified by manual microscopy using a KOVA Glasstic Slide counting chamber in which 1μl of CSF was assessed using manual light microscopy.…”
Section: Methodsmentioning
confidence: 69%
“…Further, due to the lack of electronic patient or prescribing records, the impact of the FilmArray ME panel on antimicrobial and antiviral prescribing for patients with suspicion of a CNS infection could not be confirmed. A cost analysis was not performed for the purpose of this study as this was completed for our previous study [ 18 ]. The cessation of Gram stain in our hospital was appropriate, considering only one bacterial target was missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The automated multiplex-PCR systems such as FilmArray ® System, are also emerging as useful modalities in the diagnosis of ABM, but their relatively higher cost makes their utility less feasible. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…New qualitative multiplexed techniques such as FilmArray Meningitis and Encephalitis Panel allow the study of up to 14 pathogens in 1 hour with a high sensitivity and specificity. 75 Studies have shown that the percentage of CNS aetiological diagnosis were higher in the group that had multiplex PCR testing, and this approach reduced the number of molecular biology techniques required to reach a diagnosis. 76 This technique may allow more causative agents to be identified in a single step and therefore should allow clinicians to better direct therapeutic interventions.…”
Section: Talk By Dr áLvaro Bonelli Rey Juan Carlos University Hospita...mentioning
confidence: 99%